Ceramic onlay for endodontically treated mandibular molar - Roopadevi Garlapati; Bhuvan Shome Venigalla; Shekhar Kamishetty; Jayaprakash Thumu (Wolters Kluwer Medknow Publications, 2014)
Restoration of endodontically treated teeth is important for the success of endodontic treatment. In full coverage restorations, maximum amount of tooth structure is compromised, so as to conserve the amount of tooth structure partial coverage restorations, can be preferred. This case report is on fabrication of a conservative tooth colored restoration for an endodontically treated posterior tooth. A 22-year-old male patient presented with pain in the mandibular left first molar. After endodontic treatment, composite material was used as postendodontic restoration. The tooth was then prepared to receive a ceramic onlay and bonded with self-adhesive universal resin cement. Ceramic onlay restoration was periodically examined up to 2 years.